Multiple Lanthanide Helicate Clusters and the Effects of Anions on Their Configuration1. Issue 13 (20th February 2013) - Wang, Bei; Zang, Zhipeng; Wang, Haihong; Dou, Wei; Tang, Xiaoliang; Liu, Weisheng; Shao, Yongliang; Ma, Jingxin; Li, Yizhi; Zhou, Jiang
<x xml:space="preserve">Abstract</x> Shaping up your clusters: Two supramolecular clusters of multiple lanthanide helicates have been synthesized. Cluster structure is controlled by the choice of anion, with tetrahedral ClO4− producing larger circular helicates, and trigonal‐planar NO3− leading to a compact quadruple‐stranded helicate (see picture).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>